2022
DOI: 10.1111/1541-4337.12934
|View full text |Cite
|
Sign up to set email alerts
|

The applications of conventional and innovative mechanical technologies to tailor structural and functional features of dietary fibers from plant wastes: A review

Abstract: Plant food wastes generated through the food chain have attracted increasing attention over the last few years not only due to critical environmental and economic issues but also as an available source of valuable components such as dietary fibers. However, the exploitation of plant waste remains limited due to the lack of appropriate processing technologies to recover and tailor fiber functionalities. Among the different technologies developed for waste valorization, mechanical techniques were suggested to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 231 publications
(562 reference statements)
0
15
0
Order By: Relevance
“…In future studies, it is possible to explore the difference in the effect size of different doses of BP‐SDF on T2DM mice. In addition, the SDF content in banana peels was low and relevant studies have shown that the modification of dietary fiber using the assistance of extrusion puffing, steam explosion, and ultrasound could promote the conversion of IDF to SDF and effectively improve the SDF yield (Fayaz et al, 2022; Gan et al, 2021). Therefore, this modification technique could be introduced in subsequent studies to explore changes in SDF content and differences in modified effects.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, it is possible to explore the difference in the effect size of different doses of BP‐SDF on T2DM mice. In addition, the SDF content in banana peels was low and relevant studies have shown that the modification of dietary fiber using the assistance of extrusion puffing, steam explosion, and ultrasound could promote the conversion of IDF to SDF and effectively improve the SDF yield (Fayaz et al, 2022; Gan et al, 2021). Therefore, this modification technique could be introduced in subsequent studies to explore changes in SDF content and differences in modified effects.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of these materials can be enhanced through various types of modification techniques. Several technical approaches, including mechanical, chemical, enzymatic, and/or biological technologies, have been developed to disrupt plant cellular integrity and isolate fibers with altered structural, physicochemical, and functional characteristics to enhance sorption efficiency [ 68 , 69 ].…”
Section: Fibrous Plant-based Food Waste For Sorbing Heavy Metalsmentioning
confidence: 99%
“…The components of fibers vary not only in physiological activity and chemical structure from one source to another but also in their capacity to bind essential elements such as Ca, Cu, Fe, and Zn [ 66 ] and heavy metals such as As, Cd, Hg, and Pb [ 67 ]. The performance of fibers depends on several factors: physicochemical parameters, functionality, and modification technology to improve functionality [ 68 , 69 ]. Fibers are found in plant-based foods such as nuts and seeds (beans, split peas, soybeans, corn, sunflowers, barley, oats, wheat, almonds, pumpkins, lentils, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Various technologies are utilized in the defibrillation and modification of DF obtained from different plants, including dry and wet processing, enzymatic hydrolysis, microbial fermentation, and chemical and physical treatments that can be applied individually or in combination. These technologies can result in the extraction of different types of fibers as total DF, SDF, or IDF fractions, or individual constituents with different morphologies, depending on the fiber source and pretreatments (Fayaz et al., 2022). Recently, emerging technologies, such as sub and supercritical drying, ultrasound, microwave heating, high pressure, and pulsed electric field‐assisted extractions, have also been suggested by researchers for efficient extraction of DF (Soleimanian et al., 2021).…”
Section: Dietary Fibers: Definition Functions and Extraction Processesmentioning
confidence: 99%
“…On the other hand, biological methods such as enzymatic hydrolysis or microbial fermentation could be expensive since they require pure enzymes, a specific strain of microorganisms, sophisticated equipment, and controlled process conditions (Maphosa & Jideani, 2016; Soleimanian et al., 2021). However, conventional and novel (thermo) mechanical technologies including grinding, high‐speed mixing, high dynamic pressure homogenization, high‐pressure microfluidization, high‐intensity ultrasonication, high‐hydrostatic pressure, extrusion, and steam explosion have drawn more attention due to the lower environmental impacts and promising features (Fayaz et al., 2022). It has been reported that mechanical approaches can cause profound changes in fiber functionalities and hydration properties, by altering the DF composition and structural characteristics.…”
Section: Dietary Fibers: Definition Functions and Extraction Processesmentioning
confidence: 99%